Designing a Cultural-Strategic Islamic Communication Audit Model for non-transportation asset governance in PT Kereta Api Indonesia SubDIVRE 1.1 Aceh - Rakatiwi, Yolandha; Sazali, Hasan; Samosir , Hasrat Efendi (Journal of Islamic Economics Lariba, 2026)
IntroductionThe governance of non-transportation assets in state-owned railway enterprises requires not only legal and administrative control but also effective organizational communication. In Aceh, where socio-religious norms strongly influence public legitimacy, communication practices surrounding asset safeguarding and commercialization face distinctive challenges. Despite the strategic value of railway land and buildings, communication audits have not been systematically institutionalized, creating coordination gaps and social resistance.ObjectivesThis study analyzes the implementation of communication audits in managing non-transportation assets at PT Kereta Api Indonesia SubDIVRE 1.1 Aceh and formulates a culturally grounded audit model suited to Aceh’s socio-religious context.MethodThe research employs a descriptive qualitative and evaluative approach. Data were collected through in-depth interviews, participatory observation, and document analysis involving company leaders, asset managers, operational staff, commercial partners, and community representatives. Informants were selected using purposive and snowball sampling. Data credibility was strengthened through triangulation and member checks, and analysis followed an interactive model of data reduction, display, and verification.ResultsFindings indicate that communication audits are not formally structured but occur informally through meetings and routine evaluations. Internal communication remains predominantly top-down, with limited cross-unit coordination and insufficient communication competencies. Externally, while negotiation with partners is perceived as transparent, broader stakeholder engagement lacks cultural adaptation and participatory dialogue. Resistance to asset policies often stems from inadequate alignment with Acehnese values such as deliberation, communal consensus, and the mediating role of religious and traditional leaders.ImplicationsThe study proposes a Cultural-Strategic Islamic Communication Audit Model that integrates systematic planning, exploratory and focused interviews, strategic analysis, follow-up mechanisms, and participatory evaluation. Embedding local socio-religious values into communication governance can enhance transparency, legitimacy, and conflict prevention in asset commercialization.Originality/NoveltyThis research advances communication audit scholarship by contextualizing it within Islamic governance and local cultural structures, offering a model that bridges organizational communication strategy and socio-religious legitimacy in public asset management.